Enforcing flexibility in real-time wireless communications: A bandjacking enabled protocol - Bartolomeu, Paulo
Wireless communications are being applied in heterogeneous domains ranging from healthcare to industrial manufacturing. However, as wireless channels are highly unreliable, the support of applications having tight hard real-time and fault-tolerance requirements has been provided by dedicated wired communications. Recently, a technique named bandjacking has been evaluated as a feasible solution to mitigate the unreliability associated with wireless channels in contention-based communications environments. This paper builds on this technique to propose an FTT inspired protocol aiming to provide deterministic, reliable and flexible wireless communications.